Price and Liquidity Effects of Stock Split: Empirical Evidence from the Indian Stock Market - Joshipura, Mayank (Indian Journal of Finance, 2009)
EMH argues that any event which doesn’t contain any information should not affect price and as stock split seems to be only a cosmetic event, it should not lead to any abnormal return on or surrounding either announcement date or effective date. Still, sufficient evidence is available from U. S market that shows the presence of abnormal positive return on and around announcement as well as effective day and increase in variance following ex-day that means that some information content is present with stock split announcement As semi strong form of EMH argues that even if any information content is present for stock split announcement, it should be reflected on the announcement itself and nothing should be observed on or around the effective day but there are studies which have shown the presence of price effect surrounding effective data of stock split and several hypothesis have been presented to explain effect surrounding split announcement. The signaling hypothesis (Asquith, Healy, and Palepu (1989), Rankine and Stice (1997)) and the liquidity hypothesis (Baker and Powell (1993), Muscarella and Vetsuypens (1996)) are quite popular. Apart from these, several studies find that the neglected firm hypothesis provides some explanations as well (Grinblatt, Masulis, and Titman (1984), Arbel and Swanson (1993), and Rankine and Stice (1997).